2011
DOI: 10.1007/s10562-011-0642-y
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol Hydrogenolysis over Co Catalysts Derived from a Layered Double Hydroxide Precursor

Abstract: Co catalysts, obtained from a layered double Co-Zn-Al hydroxide, are highly active and stable towards the hydrogenolysis of glycerol to 1,2-propanediol (1,2-PDO) in aqueous media. The Co-673 catalyst, containing a CoO species, provided a glycerol conversion of 67.7% and a 1,2-PDO selectivity of 50.5%. The Co-873 catalyst comprising 16 nm Co nanoparticles gave a glycerol conversion of 70.6% and a 1,2-PDO selectivity of 57.8%. It was revealed that the CoO species in the Co-673 catalyst was readily converted to 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 30 publications
5
41
0
2
Order By: Relevance
“…In accord with our results, it was recently reported that the addition of Re to a Pd catalyst leads to formation of Re-Pd bimetallic particles which shows an increased conversion of glycerol and a higher selectivity to propanediols compared with the that of mono-component Pd catalysts [26]. At the same time, Co-Zn-Al [27] and RuFe/CNT [28] catalysts, were found to be highly active and stable towards the hydrogenolysis of polyols suggesting that the addition of Co and Fe as cometals can increase the activity of Pd catalysts in glycerol CTH.…”
Section: Catalytic Testssupporting
confidence: 92%
“…In accord with our results, it was recently reported that the addition of Re to a Pd catalyst leads to formation of Re-Pd bimetallic particles which shows an increased conversion of glycerol and a higher selectivity to propanediols compared with the that of mono-component Pd catalysts [26]. At the same time, Co-Zn-Al [27] and RuFe/CNT [28] catalysts, were found to be highly active and stable towards the hydrogenolysis of polyols suggesting that the addition of Co and Fe as cometals can increase the activity of Pd catalysts in glycerol CTH.…”
Section: Catalytic Testssupporting
confidence: 92%
“…95%. Co and Ni also show catalytic activity for 1,2-PDO formation from glycerol, whereas the selectivity to 1,2-PDO is lower than that of Cu because Co and Ni promote the C-C cleavage and increase ethylene glycol and/or ethanol selectivity [98,99]. In the glycerol hydrogenolysis over Among the three base metals, Cu shows the highest activity for 1,2-PDO formation.…”
Section: Reaction Route Of Glycerol Hydrogenolysis Into 12-propanediolmentioning
confidence: 98%
“…Because of the competitive formation of glycerol C-C cleavage products, such as methanol, ethanol and ethylene glycol, 1,2-PDO cannot be selectively produced over Co-and Ni-based catalysts [98,99]. The 1,2-PDO selectivities higher than 90% can be achieved over most of the Cu-supported catalysts [90][91][92][93][94][95][96][97], and Cu with small particle sizes is preferable for 1,2-PDO formation [91][92][93][95][96][97].…”
Section: Liquid-phase Glycerol Hydrogenolysis Into 12-pdo Over Base mentioning
confidence: 99%
“…In addition to Cu catalysts, there are studies showing that Raney nickel (182), Ni/AC (183), Ni/NaX (184), Ni/SiO 2 -Al 2 O 3 (185), Co/MgO (186), Ni/Mg/Al, Ni/Co/Mg/Al, and Co/Zn/Al layered double hydroxides (180,187) had relatively good activity in the hydrogenolysis of glycerol to 1,2-propanediol (Table 2). Particularly, in the presence of a Raney nickel catalyst using crude glycerol from biodiesel production as the feedstock for the hydrogenolysis was found to be possible (182).…”
Section: Supported Cu and Ni Catalystsmentioning
confidence: 99%